The bonus-driven "rainmaker" financial firm: How these firms enrich top employees, destroy shareholder value and create system financial instability - James Crotty (University of Massachusetts, Department of Economics, 2009)
We recently experienced a global financial crisis so severe that only massive rescue operations by governments around the world prevented a total financial market meltdown and perhaps another global Great Depression. One necessary precondition for the crisis was the perverse, bonus-driven compensation structure employed in important financial institutions such as investment banks. This structure provided the rational incentive for key decision makers in these firms (who I call 'rainmakers') to take the excessive risk and employ the excessive leverage in the bubble that created the preconditions for the crisis. This paper presents and evaluates extensive data on compensation practices in investment banks and other important financial institutions. These data show that rainmaker compensation has been rising rapidly, is very large, and has asymmetric properties that induce reckless risk-taking. Since boom-period bonuses do not have to be returned if rainmaker decisions eventually lead to losses for their firms, and since large bonuses continue to be paid even when firms in fact suffer large losses, it is rational for rainmakers to use unsustainable leverage to invest in recklessly risky assets in the bubble. A review of the modest literature on financial firm compensation practices in general and those of investment banks in particular demonstrates that the giant bonuses of the recent past are not efficient returns to human capital - they are unjustified rents. The paper discusses possible answers to the challenging questions: what is the source of rainmaker rents and how are they sustained over time? Answers to these questions can help guide debates over the appropriate regulation of financial markets. They are also necessary inputs to the development of an adequate theory of the 'rainmaker' financial firm that can help us understand how these firms were able to maximize the compensation of their key employees through policies that destroyed shareholder value and created systemic financial fragility. To my knowledge, no such theory currently exists.
Keywords: G01; G24; G10; 330; bonuses; investment banks; leverage; financial crisis; perverse incentives